Electronic information access and utilization by Makerere University students in Uganda - Obura, Constant Okello; Magara, Elisam (My University, 2008)
The objectives of this study were to establish the level of computer utilization skills of Makerere University (Uganda) Library and Information Science (LIS) students; to determine the use of electronic information resources by LIS students; to determine the attitudes of LIS students towards electronic information resources; and to establish the problems faced by LIS students in accessing electronic information resources.
Keywords: Electronic Information Resources, Electronic Information Access, E-resources, Makerere University Library, Makerere University, Library and Information Science Students